2021
DOI: 10.1088/1755-1315/948/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activities of several extracts endophytic Pseudomonas azotoformans UICC B-91

Abstract: Pseudomonas azotoformans known for the benefit on agriculture area as soil fertility enhancer. Pseudomonas azotoformans UICC B-91 was successfully isolated from tissues of N. altissima which traditionally known for treating infectious diseases. Therefore, endophytic P. azotoformans might contain antimicrobial compound. This research aims on exploring the antimicrobial activities of several extracts P. azotoformans UICC B-91 against pathogenic microbes. Isolates were extracted with dichloromethane, chloroform, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…20 F1 also has strong anticandidal activity than its antibacterial activity. 4 Therefore, this identification compound supported that F1 has a potential as anticandidal compound.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…20 F1 also has strong anticandidal activity than its antibacterial activity. 4 Therefore, this identification compound supported that F1 has a potential as anticandidal compound.…”
Section: Discussionmentioning
confidence: 55%
“…18,27 From our previous research, F3 also have antibacterial and anticandidal activity. 4 The interesting study was reported on cytotoxic activity of sarmentine, but indeed its activity was still lower than taxol as positive control. 17 From our observation, there hasn't any publication on sarmentine from Pseudomonaceae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and extraction of the bioactive compounds from P. azotoformans UICC B-91 was carried out following the method of Oktarina et al [13] with modifications. The starter was prepared by inoculating one dose of P. azotoformans UICC B-91 from NA medium obliquely into 20 mL RB in a 150 mL Erlenmeyer flask, followed by incubation in an incubator shaker for 24 hours at 30 °C at 100 rpm.…”
Section: Isolation and Extraction Of Active Antifungal Compoundsmentioning
confidence: 99%